Change and instability in production and yield of rice in Bangladesh - Farhana, Zaki; Uddin, Md Taj (Research in Agriculture Livestock and Fisheries, 2018)
Rice is considered as one of the monumental sources of human energy in Bangladesh. It can be stated that a vital element by which agronomic sector has been earned most of the quantity of profits for national development in this country is rice. This study covers the data of rice including the time from 1972 to 2016 has been collected from secondary sources of Bangladesh Bureau of Statistics. Different statistical tools have been used to complete the analysis. The analysis reveals that area, production and yield of rice has increased significant during the study period. The growth rate of production is significantly higher than the growth rate of area and yield. Despite the production has been increased, It is not enough to full fill the demand of the country. It is observed that area, production and yield are not stable. Therefore, researchers, government, nongovernment organization and policy makers should come forward to improve this sector. By this way new ideas and findings could be generated in order to improve the growth of rice. Res. Agric., Livest. Fish.5(3): 321-326, December 2018